Impact of Capital Structure, Firm Size, and Inflation on Profitability: The Moderating Role of Good Corporate Governance in Energy Firms - Ahmad Qodri; Fanji Farman (AIBPM Publisher, 2026)
Profitability in energy sector companies is influenced by financing decisions, firm scale, macroeconomic conditions, and governance quality. This study examines the effects of capital structure, firm size, and inflation on profitability, with good corporate governance (GCG) as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange during 2020–2024. Using a quantitative approach, this study analyzes 47 companies selected through purposive sampling, resulting in 235 firm-year observations. Data were analyzed using panel data regression and Moderated Regression Analysis with EViews 13. The Random Effect Model was selected based on the Hausman test (p = 0.4497) and Breusch-Pagan LM test (p = 0.0000). The results show that capital structure negatively affects profitability (? = -0.011929; p = 0.0174), while firm size (? = 0.019412; p = 0.0133) and inflation (? = 0.023036; p = 0.0001) have positive effects. GCG does not directly affect profitability (p = 0.8948). However, GCG significantly moderates the firm size–profitability relationship (? = -0.057456; p = 0.0323), weakly moderates capital structure–profitability (p = 0.0515), and does not moderate inflation–profitability (p = 0.6020). These findings suggest that energy firms should optimize debt management, scale efficiency, and governance implementation beyond compliance.